1990
DOI: 10.1111/j.1439-0450.1990.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Studies on the Occurrence of Listeria monocytogenes in the Feces of Dairy Cattle

Abstract: Summary Seasonal variation in the fecal shedding of Listeria spp. in dairy cattle was examined by collecting a total of 3,878 fecal samples during a period of two years. The prevalences of Listeria spp. and L. monocytogenes were higher during the indoor season (12.7% and 9.2%, respectively) than in samples collected from the animals on pasture (5.3 % and 3.1 %, respectively). The highest frequencies of Listeria spp. (19.4%) and L. monocytogenes (16.1 %) were detected in December. Listeriae were isolated from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
61
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 16 publications
15
61
2
1
Order By: Relevance
“…Consecutive isolation of L. monocytogenes from two farms Table 4. Relationship between isolation of L. monocytogenes from silage samples and their pH domestic species, the organisms are often found in the intestines of healthy cows as well as in the environment (1,7,8,16,17). This study also confirmed the presence of L. monocytogenes in areas where there had been no reports of listeriosis.…”
Section: Incidence Of L Monocytogenes In Silage In Relation To Phsupporting
confidence: 76%
“…Consecutive isolation of L. monocytogenes from two farms Table 4. Relationship between isolation of L. monocytogenes from silage samples and their pH domestic species, the organisms are often found in the intestines of healthy cows as well as in the environment (1,7,8,16,17). This study also confirmed the presence of L. monocytogenes in areas where there had been no reports of listeriosis.…”
Section: Incidence Of L Monocytogenes In Silage In Relation To Phsupporting
confidence: 76%
“…Differences in sampling and analytical methods can also give rise to variability in L. monocytogenes prevalence. Overall prevalence below 10% is commonly reported when individual animals are sampled from several (Husu, 1990) or only one herd (Vilar et al, 2007). However, prevalence values above 20% for faecal shedding of L. monocytogenes have been reported in healthy cattle from several herds (Nightingale et al, 2004;Esteban et al, 2009).…”
Section: Healthy Animalsmentioning
confidence: 99%
“…were obtained from the sheep and cow's milks, bulk tank milks and silage samples examined. Similarly, a low prevalence (0-5%) of L. monocytogenes in bulk tank milk has been reported from countries such as India (1), Sweden (36), Canada (7), Spain (10), and Finland (15). In contrast, some authors reported a greater prevalence of Listeria spp.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies reported that Listeria spp. were found between 0.5% and 67% of the isolation rate in cattle and sheep feces (15,29,30,35,37). Our findings were also in this range.…”
Section: Discussionmentioning
confidence: 99%